Influence of Principal Management Practices of Academic Progress Records on Students’ Academic Performance in KCSE in Public Schools in Mashuru Sub-County - Muasa, Damaris Mwikali; Ogola, Fredrick; Nzioki, Susan (Machakos University Press, 2021)
The purpose of the study was to determine the influence of principals’ management practices of academic progress records on students’ academic performance in KCSE in public schools in Mashuru Sub-County. According to records available from the office of the Kajiado County Director of Education, the performance of students in KCSE in Mashuru Sub-County has not only been poor but also spiralling downwards. This has culminated in only 23 students attaining a grade of C+ in a period of four years. The minimum grade for university entry for KCSE graduates is C+ whereas majority of the candidates in the subcounty are scoring below D+. The study utilized a descriptive research design. The target population consisted of 45 principals, 540 teachers and 585 student leaders totalling to 1170. Simple random sampling was employed to select a sample size of 13 principals, 54 teachers and 56 student leaders. Data was collected by use of interview schedule for principals and questionnaires for teachers and student leaders. The collected data was analysed using descriptive statistics consisting of frequencies and percentages with the help of SPSS. The study concluded that that principals’ management practice of academic progress records influence students’ academic Performance in KCSE in public secondary schools, hence compromising the quality of examination grades achieved in the sub-county. From the students, it was established that this activity had no definite time in many schools and the principals cited that they were facing a number of challenges which hindered efficiency in the practice of management of academic progress records, translating poor academic results. The findings of the study will help the Ministry of Education in formulating of assessment modules for students’ academic progress as well as empower the principals to enhance performance.
Keywords: Principals’ Management Practice; Academic Progress Records; Students’ Academic Performance in KCSE; Public Secondary Schools